Influence of Teacher Attributes on the Use of Resources in Teaching English Grammar - Odutayo, Adesegun Olayide; Ishola, Abdulkareem Farooq; Adewuyi, Habeeb Omoponle (Universitas Islam Negeri Walisongo Semarang, 2024)
English is a critical subject at every stage of the Nigerian educational system, so it is imperative to guarantee success that corresponds with the substantial resources and time invested in teaching and studying. This research looked at the influence of teachers' attributes on using resources to teach English grammar in English by adopting a descriptive survey research design. All English language instructors employed in public and private secondary schools in Ilorin were the subject of this investigation. This study’s sample comprised 268 English language instructors. A questionnaire created by the researchers was utilized. The data gathered was subjected to reliability assessment using Pearson’s Product Moment Correlation (PPMC). There was a 0.81 correlation coefficient. Mean and percentage were chosen to respond to the study questions posed. The One-Way Analysis of Variance (ANOVA) and the independent t-test were used to evaluate the generated hypotheses at the 0.05 significant level. The results show that the most regularly utilized resources for teaching English grammar were print materials and textbooks, audiovisual aids, models and manipulatives, and digital technologies. It was recommended that curriculum designers continue to promote more realistically oriented materials, as this will help to engage students more and support the efforts of teachers.